2014
DOI: 10.1093/infdis/jiu051
|View full text |Cite
|
Sign up to set email alerts
|

Dolutegravir in Antiretroviral-Experienced Patients With Raltegravir- and/or Elvitegravir-Resistant HIV-1: 24-Week Results of the Phase III VIKING-3 Study

Abstract: Background. The pilot phase IIb VIKING study suggested that dolutegravir (DTG), a human immunodeficiency virus (HIV) integrase inhibitor (INI), would be efficacious in INI-resistant patients at the 50 mg twice daily (BID) dose.Methods. VIKING-3 is a single-arm, open-label phase III study in which therapy-experienced adults with INI-resistant virus received DTG 50 mg BID while continuing their failing regimen (without raltegravir or elvitegravir) through day 7, after which the regimen was optimized with ≥1 full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
254
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(277 citation statements)
references
References 14 publications
18
254
1
4
Order By: Relevance
“…7B). This is consistent with reports that the preexistence of Q148 ϩ Ն1 resistance substitutions, but not Q148 mutations alone, were statistically associated with lower success rates in the clinic with DTG than when this drug was used in first-line therapy (56). The G118R variant enzyme displayed low-level resistance against all INSTIs, also in agreement with tissue culture resistance studies using TZM-bl cells (12) and with data on HIV-1 (32,53).…”
Section: Discussionsupporting
confidence: 90%
“…7B). This is consistent with reports that the preexistence of Q148 ϩ Ն1 resistance substitutions, but not Q148 mutations alone, were statistically associated with lower success rates in the clinic with DTG than when this drug was used in first-line therapy (56). The G118R variant enzyme displayed low-level resistance against all INSTIs, also in agreement with tissue culture resistance studies using TZM-bl cells (12) and with data on HIV-1 (32,53).…”
Section: Discussionsupporting
confidence: 90%
“…The most recently approved INSTI dolutegravir (DTG) is for once-daily dosing without a pharmacokinetic booster and shows efficacy for treatment-naive subjects and treatment-experienced but INSTI-naive subjects, as well as subjects who failed RAL and EVG treatment (9)(10)(11)(12)(13). DTG was approved by the U.S. FDA in August 2013 for treatment-naive and treatment-experienced INSTI-naive adults, as well as for INSTI-resistant adults.…”
mentioning
confidence: 99%
“…The INSTI-resistant patient VIKING pilot study and phase 3 (VIKING-3) study have shown the clinical utility of DTG in patient populations who have failed to respond to INSTI therapy (10,18,19).…”
mentioning
confidence: 99%
“…There is also a high degree of cross-resistance between RAL and EVG, since the major resistance substitutions for RAL are located at positions G140, Y143, Q148, and N155, while those for EVG are located at positions T66, E92, G140, S147, Q148, and N155 (1,3). Although resistance during initial therapy has not yet been reported for DTG, patients can fail DTG therapy if they were previously treated with RAL or EVG and possess relevant mutations for these drugs (4)(5)(6).…”
mentioning
confidence: 99%